2018
DOI: 10.26444/aaem/74406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental pollution with aromatic hydrocarbons on endocrine and metabolic functions of the human placenta

Abstract: The course of pregnancy in the environment with elevated levels of aromatic hydrocarbons leads to impaired placental functioning and reduced endocrine and metabolic activity of the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Pollutants switch the activity of AhR toward their own metabolism instead of those of endogenous compounds, such as retinol, for example. Similar reasoning has been put forward to explain how elevated levels of aromatic hydrocarbons may lead to impaired placental functioning by reducing the endocrine (gonadotropin, estrogen receptor, and hPL) and metabolic (glutathione transferase, phosphatase, and LDH) activities of the placenta [63].…”
Section: Discussionmentioning
confidence: 89%
“…Pollutants switch the activity of AhR toward their own metabolism instead of those of endogenous compounds, such as retinol, for example. Similar reasoning has been put forward to explain how elevated levels of aromatic hydrocarbons may lead to impaired placental functioning by reducing the endocrine (gonadotropin, estrogen receptor, and hPL) and metabolic (glutathione transferase, phosphatase, and LDH) activities of the placenta [63].…”
Section: Discussionmentioning
confidence: 89%
“…Wierzba and Radowicki have shown that the endocrine activity of the placental tissue and the metabolic activity obtained after delivery from women with elevated levels of phenol and 1-hydroxypyrene in the excreted urine is statistically significantly lower compared to patients who are not exposed to aromatic hydrocarbons [28].…”
Section: Resultsmentioning
confidence: 99%
“…In the second phase of biotransformation, the resulting phenolic compounds from the metabolization reactions are conjugated to glutathione, glucuronides, and sulfate esters to enhance the aqueous solubility to finally be excreted in urine ( 38 ). B[a]P (five-ring) is a member of the PAH family that can accumulate in the placenta ( 39 , 40 ) inhibiting trophoblast cells differentiation and proliferation ( 41 ), disrupting the endocrine placental function ( 42 ), disturbing the redox balance ( 39 ) and forming DNA adducts ( 43 ).…”
Section: Air Pollutionmentioning
confidence: 99%